Strategy for Improving Employee Performance based on Organizational Structure Changes at the West Java Climatological Station - Misbahudin, Dadang; Ramly, Amir Tengku; Putra, Awang Darmawan; Sofianti, Evin (PT FORMOSA CENDEKIA GLOBAL, 2024)
Bureaucratic reform aims to accelerating better governance, improve institutional performance to individual state civil apparatus (ASN) including by simplifying the organizational structure, one of which is at the West Java Climatology Station, This study aims to analyze and compile a priority scale of employee performance improvement strategies at the West Java Climatology Station using the Analytic Hierarchy Process method based on the opinions of climatology, organization management and HR experts, resulting in findings that indicators of variable factors set priorities 1. Employee discipline, 2. teamwork, 3. ease of public service, 4. use of information technology, 5.competence and expertise, 6.simple SOPs, 7.simplification of organizational structure, 8.work system adjustments and 9. work culture, The results of the study are expected to guide strategies to achieve performance targets in each BMKG UPT, further research is needed regarding performance improvement due to simplification of the new organizational structure which has been running since the beginning of 2023.